Capillary Electrophoresis Measurements of Electrophoretic Mobility for Colloidal Particles of Biological Interest - Glynn, J. R. (American Society for Microbiology, 1998)
The electrophoretic mobilities of three bacterial strains were investigated by capillary electrophoresis (CE) and were compared with results obtained by microelectrophoresis (ME). The CE measurements yielded bimodal electropherograms for two of the strains, thus illustrating for the first time that surface charge variations within a monoclonal population can be probed by CE. Intrapopulation variations were not detected by ME. The mobilities of three chemically distinct types of latex microspheres were also measured. Differences between the mean mobilities obtained by CE and ME were not statistically significant (P ≤ 0.50); the standard deviations of the CE measurements were typically 2 to 10 times smaller than those obtained by comparable ME measurements. The reproducibility of CE permitted batch-to-batch mobility variations to be probed for the bacteria (one of the strains exhibited such variations), and aggregation was evident in one of the latex suspensions. These effects were not measurable with ME.